1999
DOI: 10.1080/10408449991349221
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology of Hydroquinone — Relevance to Occupational and Environmental Exposure

Abstract: Hydroquinone (HQ) is a high-volume commodity chemical used as a reducing agent, antioxidant, polymerization inhibitor, and chemical intermediate. It is also used in over-the-counter (OTC) drugs as an ingredient in skin lighteners and is a natural ingredient in many plant-derived products, including vegetables, fruits, grains, coffee, tea, beer, and wine. While there are few reports of adverse health effects associated with the production and use of HQ, a great deal of research has been conducted with HQ becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
1
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 312 publications
(335 reference statements)
4
129
1
7
Order By: Relevance
“…24,32 Phenol and hydroquinone produce genetic damage of the type found in leukemia Quinones derived from phenol, catechol, hydroquinone and 1,2,4-benzenetriol cause various forms of genetic damage Leukemia including chromosome breakage and aneuploidy. 26,33 Aneuploidy is the loss or gain of whole chromosomes and is a frequent clonal aberration in leukemia. Common aneuploidies include trisomy of chromosome 8 and monosomy of chromosomes 5 and 7.…”
Section: Figurementioning
confidence: 99%
“…24,32 Phenol and hydroquinone produce genetic damage of the type found in leukemia Quinones derived from phenol, catechol, hydroquinone and 1,2,4-benzenetriol cause various forms of genetic damage Leukemia including chromosome breakage and aneuploidy. 26,33 Aneuploidy is the loss or gain of whole chromosomes and is a frequent clonal aberration in leukemia. Common aneuploidies include trisomy of chromosome 8 and monosomy of chromosomes 5 and 7.…”
Section: Figurementioning
confidence: 99%
“…HQ is an oxidant of special relevance due to its presence not only in cigarette smoke but also in processed foods, plastic containers, and atmospheric pollutants as well as its widespread occurrence in nature. 16,17 Detectable levels of HQ have been measured in the plasma of many nonsmoker individuals living a Western life style. 16 We embrace the pathogenic paradigm based on the response-to-injury hypothesis, which proposes that sub-RPE deposits originate from RPE-derived cell membrane blebs 18,19 induced by chronic nonlethal injury to the RPE in response to oxidative damage.…”
mentioning
confidence: 99%
“…Recent studies suggested the possibility of serious adverse events associated with HQ, 1,[8][9][10] and various types of skinlightening agents have been proposed including gentisic acid analogues, 9) HQ glucosides 11) and tert-butyl HQ. 12) New protocols or formulation methods have also been proposed using all-trans retinoic acid, kojic acid and hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…1,9) Recent investigations have suggested the nephrotoxicity, mutagenicity or carcinogenicity of HQ. 1,[8][9][10] However, the adverse events associated with external OTC use of HQ in FDA-regulated products have been limited to a small number of cases of exogenous ochronosis, whereas higher incidences have been reported with inappropriate use of unregulated OTC products containing higher HQ concentrations. 1) In Japan, HQ formulations are not commercially available and have been prepared by extemporaneous nonsterile compounding in hospitals with various prescriptions without sufficient experimental evidence providing justification for the prescriptions.…”
mentioning
confidence: 99%
See 1 more Smart Citation